Development of nanostructured material for water treatment - Tan, Benny Yong Liang. (2012)
Arsenic is a toxic substance that can be found in various groundwater bodies which include mainly arsenite As (III) or arsenate As (V). As (III) has a higher toxicity, as well as, higher difficulty to be removed as compared to its counterpart, As (V). Many reports have addressed that the presence of unhealthy concentration of arsenic can be found in various countries water bodies. However, there is currently no simple treatment to remove As (III) efficiently, therefore, an oxidation process is always necessary to obtain a higher removal efficiency. At present, adsorption is considered as one of the promising technology to remove dissolved arsenic from water sources.